Review of the Use of the Countercyclical Capital Buffer in the Eea in Response to the SARS-CoV-2 Virus Pandemic Outbreak - Petryka, Piotr (Journal of Finance and Financial Law, 2021)
The purpose of the article is to verify how the SARS-CoV-2 virus pandemic outbreak influenced the decisions to apply the countercyclical capital buffer in the EEA and whether, based on the experience gained so far in applying the countercyclical capital buffer in the EEA, it is possible to clearly distinguish between the models of its application. Methodology used to achieve this, was to built the field of research and to perform a comparative analysis of macroeconomic data on the application of the above-mentioned instrument in the EEA during the COVID-19 pandemic crisis. Results of the research are two methods and two variants of the application of the countercyclical capital buffer that were distinguished and named, indicating the benefits and challenges of using each of them. Moreover, the limited usefulness of the standardized and additional gap was confirmed in the light of the conducted research, available in the literature. The article concludes with recommendations for further research.